HEURISTIC METHOD FOR LOW POWER RACE-FREE STATE-ASSIGNMENT OF AN ASYNGHRONOUS AUTOMATON - Yu. V. Pottosin (Informatika)
The problem of race free state-assignment of an asynchronous automaton minimizing the switching activity of memory elements in an implementing circuit is considered. A heuristic method to solve this problem for an asynchronous automaton is suggested where the critical races between memory elements of the implementing circuit are eliminated.